ANEMIA GIZI BESI PADA IBU HAMIL DI WILAYAH PUSKESMAS SAWANG KABUPATEN ACEH UTARA TAHUN 2007 - Sahara, Eva (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2011)
Eva Sahara, SKM1, dr. H. Syarifuddin Anwar, SKM2Peminatan Gizi, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245Peminatan AKK, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245 AbstractThe iron deficiency anemia in pregnant women is one of the nutrition problems that should deserve special attention and serious treatment. In 2006, 386 (58%) out of 667 pregnant women in the Puskesmas working area of sawang sub district, Kabupaten Aceh Utara suffered from iron deficiency anemia. This high percentage indicated the area had a serious problem of pregnant women. The quality of nutritional status of pregnant women is one of the indicators to determine the quality of human resources in the future. This descriptive analytic research by using cross sectional design conducted from 19 March to 4 April 2007 in Puskesmas Sawang. A purposive sampling as well as chi-square test was used to analyze the data with the alpha 0.05. Results of uni-variation analysis showed that 69.8% respondent suffered from iron deficiency anemia. From the results of bi-variation analysis found that there was relationship between level of education, knowledge about nutrition, eating habits, consumption of iron tablets and family income of respondents with anemia (p value 0.05). Low level of education is a very dominant factor for respondent to get risk of anemia. It is recommended to increase knowledge of respondent on how importance of taking sufficient iron tablets regularly during pregnancy to prevent iron deficiency anemia. It is also necessary for Puskesmas staff of Sawang to increase counseling activities on the benefits of iron tablets to pregnant women and their husband, the community and religious leaders during pregnancy.Keywords : iron deficiency anemia, pregnant women, hemoglobin test, iron teblets